Identification of proteins from human permanent erupted enamel (2015)
Proteins from the extracellular matrix of enamel are highly specific and necessary for proper enamel formation. Most proteins are removed from the matrix by enamel proteases before complete mineralization is achieved; however, some residual protein fragments persist in the mineralized matrix of erupted enamel. So far, only amelogenin peptides obtained by traditional bottom‐up proteomics have been recovered and identified in human permanent erupted enamel. In this study, we hypothesize that other enamel‐specific proteins are also found in human permanent enamel, by analysing human erupted third molars. Pulverized enamel was used to extract proteins, and the protein extract was subjected directly to liquid‐chromatography coupled to tandem mass spectrometry (LC ‐MS /MS ) without a previous trypsin‐digestion step. Amelogenin and non‐amelogenin proteins (ameloblastin and enamelin) were succesfully identified. The sequences of the naturally occurring peptides of these proteins are reported, finding in particular that most of the peptides from the amelogenin X‐isoform come from the tyrosine‐rich amelogenin peptide (TRAP ) and that some were identified in all specimens. In conclusion, our LC ‐MS /MS method without trypsin digestion increased the coverage of identification of the enamel proteome from a few amelogenin peptides to a higher number of peptides from three enamel‐specific proteins.